2021
DOI: 10.3389/fchem.2021.733881
|View full text |Cite
|
Sign up to set email alerts
|

Highly N2-Selective Activated Carbon-Supported Pt-In Catalysts for the Reduction of Nitrites in Water

Abstract: The catalytic reduction of nitrites over Pt-In catalysts supported on activated carbon has been studied in a semi-batch reactor, at room temperature and atmospheric pressure, and using hydrogen as the reducing agent. The influence of the indium content on the activity and selectivity was evaluated. Monometallic Pt catalysts are very active for nitrite reduction, but the addition of up to 1 wt% of indium significantly increases the nitrogen selectivity from 0 to 96%. The decrease in the accessible noble metal s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 41 publications
(58 reference statements)
1
9
0
Order By: Relevance
“…Moreover, the addition of Pd and In in different steps represented a distribution of the particles on the surface in a way that favored the selectivity toward N 2 . In this sense, it is reasonable that the PIACR catalyst presented the lowest selectivity to N 2 since it showed good distribution of Pd and In on the support surface, and generally, the selectivity to N 2 was higher for catalysts with lower dispersion (Yoshinaga et al 2002;Garron et al 2005;Zhang et al 2008;Soares et al 2021).…”
Section: Selectivity Of the Most Active Catalystsmentioning
confidence: 88%
See 1 more Smart Citation
“…Moreover, the addition of Pd and In in different steps represented a distribution of the particles on the surface in a way that favored the selectivity toward N 2 . In this sense, it is reasonable that the PIACR catalyst presented the lowest selectivity to N 2 since it showed good distribution of Pd and In on the support surface, and generally, the selectivity to N 2 was higher for catalysts with lower dispersion (Yoshinaga et al 2002;Garron et al 2005;Zhang et al 2008;Soares et al 2021).…”
Section: Selectivity Of the Most Active Catalystsmentioning
confidence: 88%
“…These factors, in turn, depend on the preparation method and the metal loading (Martínez et al 2017). On the other hand, Pd particle size considerably affects the selectivity to N 2 , with better selectivity being obtained in the presence of metallic agglomerates (Yoshinaga et al 2002;Garron et al 2005;Zhang et al 2008;Soares et al 2021). Marchesini et al (2008) and Zhang et al (2008) found that selectivity was greatly correlated to the size of active metal particles.…”
Section: Alumina-supported Catalystsmentioning
confidence: 99%
“…Nitrite is a common chromogenic agent and preservative in meat food because it can not only make the color of meat look better, but also inhibit the generation of botulinum toxin [ 1 ]. However, the excessive intake of nitrite will lead to methemoglobinemia [ 2 ] and gastric cancer [ 3 ]. Therefore, monitoring whether the amount of nitrite in food is excessive is essential to protect human health, requiring the accurate and timely monitoring of nitrite in food samples.…”
Section: Introductionmentioning
confidence: 99%
“…Adsorption is one of the most effective methods to treat organic dyes, and it is widely used because of its relatively low cost and easy operation. Various adsorbents have been designed to remove dyes in water and have considerable adsorption capacities, such as activated carbon ( Tang et al, 2017 ; Zhang et al, 2019 ; Soares et al, 2021 ), functional carbon materials ( Magno et al, 2020 ; Xing et al, 2020 ; Zhang et al, 2020 ), composite hydrogel ( Srivastava and Roy Choudhury, 2021 ), and metal oxide ( Rastogi et al, 2017 ; Xu et al, 2020 ; Şerban and Enesca, 2020 ). Among these methods, chemistry reduction has gained popularity because of its ease of use, high efficiency, clean processing, and low cost.…”
Section: Introductionmentioning
confidence: 99%